Imaging Characteristics of Sigmoid Sinus Wall Anomalies, Idiopathic Intracranial Hypertension, and Spontaneous CSF Leaks. Issue 6 (July 2021) - Bhatnagar, Kavita; Patel, Lakir; Gourishetti, Saikrishna; Raghavan, Prashant; Eisenman, David J.
Abstract : Objective: To assess the frequency of radiographic features of elevated intracranial pressure (ICP) in patients with sigmoid sinus wall anomalies (SSWA) and compare to those in idiopathic intracranial hypertension (IIH) and spontaneous CSF (sCSF) leaks. Study Design: Retrospective review. Setting: Tertiary care center. Patients: 110 patients - 62 SSWAs, 19 IIH, 29 sCSF leaks. Main Outcome Measures: Demographics, comorbidities and radiographic features by diagnosis. Results: Imaging findings indicative of elevated ICP were similar across all three groups, as were body mass index, hyperlipidemia and diabetes. On univariate analysis, sCSF leak patients were significantly older than SSWA (60 vs. 41 years, p < 0.001) and IIH (60 vs. 40 years, p < 0.001) patients. They had a greater prevalence of arachnoid granulations than SSWA (75.8% vs. 37.1%, p < 0.01) and tegmen dehiscence than both SSWA and IIH (93.1% vs. 75.8% vs. 57.8%, p = 0.01), though a lower prevalence of empty sella than SSWA (44.8% vs. 72.5%, p < 0.001). SSWAs were present in roughly 44.3% of IIH and sCSF leak patients, and IIH in roughly 15.8% of SSWA and sCSF leak patients. Age (OR = 1.1, p = 0.001), hypertension (OR = 8.3, p = 0.01) and empty sella (OR = 0.1, p = 0.01) were predictive of sCSF leaks compared to SSWAs on multivariate analysis. Conclusions: Many radiographic and clinical features of elevated ICP are found at similar rates among patients with SSWA, IIH and sCSF leaks, suggesting a common underlying process. SSWAs seem to present earlier along this spectrum of phenotypes, while sCSF leaks present later. Differences in age, metabolic syndrome and ICP may influence a patient's clinical presentation.